Structure-Based Computational Screening of Indonesian Spice-Derived Compounds Targeting the Neuropeptide Y1 Receptor - Woran, Blessari Tesalonika; Jollie, Jessica Angelina; Dharmasetiawan, Michael Nathanael; Kusnadi, Kevin Purwadinata (Indonesian Journal of Life Sciences, 2026)
The neuropeptide Y1 receptor (NPY1R) is a promising therapeutic target for type 2 diabetes mellitus (T2DM) due to its role in regulating appetite and insulin secretion. Indonesian spices contain diverse bioactive compounds with potential metabolic effects, yet their interaction with NPY1R remains largely unexplored. This study aimed to identify potential natural allosteric modulators of NPY1R using structure-based virtual screening and pharmacokinetic analysis. A total of 17,356 compounds from the NCBI PubChem database were pre-filtered, yielding 860 ligands for blind molecular docking. Of these, 97 showed stronger predicted binding affinities than the reference antagonist BMS-193885. Further screening based on physicochemical properties, toxicity, and ADMET parameters identified six top candidates. Among them, cis-theaspirone demonstrated the most favorable profile, including binding to an allosteric pocket (–10.0 kcal/mol; RMSD 2.658 Å), high gastrointestinal absorption, blood–brain barrier permeability, and acceptable solubility. Molecular dynamics simulations over 50 ns confirmed stable ligand–receptor interactions. Overall, cis-theaspirone emerges as a potential NPY1R modulator, highlighting the promise of Indonesian spice-derived compounds for further investigation in metabolic disease research.